Can Appendiceal Neoplasms Be Predicted in Patients with Presumed Acute Appendicitis? - Pedük, Şevki (European Journal of Therapeutics, 2024)
Objective: The detection of malignancy in the final pathology report of patients undergoing surgery for acute appendicitis is a nasty surprise for both the patient and the clinician. To improve the management of this situation, we analyzed clues for predicting possible neoplasms. Methods: We analyzed in detail the data of patients operated on in our department with a preliminary diagnosis of acute appendicitis over 42 months. The group whose final pathology was reported as primary appendiceal neoplasm was compared with the acute appendicitis group. Results: Appendiceal neoplasm was detected in 16 patients (1%). Half of these were mucinous epithelial neoplasms. Neuroendocrine tumors (18.7%) were the second most common neoplasm. According to the logistic regression model, low hemoglobin level (p<0.01) and low Alvarado score (p:0.02) were the two most valuable factors in the prediction of primary appendiceal neoplasms. Laboratory findings of high neutrophil/lymphocyte ratio (p<0.01) and plastron formation on imaging (p:0.03) were more common in the neoplasm group. Advanced age, comorbidity, immunosuppression and inflammatory bowel diseases (IBD) were other characteristics of the neoplasm group. Conclusions: Appendiceal neoplasms should always be considered in anemic patients with relatively low Alvarado scores.